The Influence of Housing Habitability on Familial Coexistence Patterns - Corral Verdugo, Víctor (Consorcio de Universidades Mexicanas A.C., 2012)
Based upon antecedents showing that a negative housing habitability propitiates inter-partner violence as well as child maltreatment, we aimed at studying the processes that are opposite to family violence and a bad habitability. This study investigated the possible influence of adequate housing habitability on the positive functioning of Mexican families. Two-hundred-and-five inhabit- ants from a northern Mexican city responded to an instrument assessing the two above-mentioned variables. The assessed habitability conditions included noise control, pleasant temperature, a lack of overcrowding, appropriate illumination, depth, and privacy. In turn, positive family func- tioning considered situations such as family support, family members’ communication, democratic decision-making, flexibility, display of affection, acceptance and respect of everybody’s opinions, among others. A structural equations model revealed a significant correlation between housing habitability and positive family functioning, which suggests that the physical conditions of a house could shape important elements stimulating a healthy interaction among family members, as well as their well-being.